Negocio de reciclaje de botellas plásticas mediante el uso de Reverse Vending Machine (RVM) - Barycki Korytkowski, Hendryk Cheslavo (2022)
The proposed thesis aims to illustrate the implementation of a business based on an automatic recycling system that provides incentives for users through RVM (Reverse Vending Machines), whose objective is to increase the formal recycling of PET bottles in Lima. To ensure the success of the implementation, the scope is limited to Modern Lima, implementing 30 RVMs during the first 3 years of the project, which will be strategically distributed in Shopping Centers, Supermarkets, as well as other premises that ensure accessibility for users and a high influx. The sustenance of the business is based on contributions from the sale of advertising space, supporting the support chosen by advertisers with the high content of social responsibility that the project implies, which generates a positive perception in consumers and users, which we hope will be each. increasingly sensitive to the problems of ocean pollution, caused by plastic waste. The RVM, which will be imported at the request of China, will be managed by a system that will allow the registration of user information and recycled material, as well as the discount and benefits scheme offered to the user that will be provided by the sponsoring companies, thus promoting the rotating their products and benefiting from the social impact of RVMs. The monthly income from advertising per machine is estimated at US $ 1,200 per month and will cover operating expenses, including operating costs, leaving an economic rate of return of 33% and a financial return of 35%.